2010
DOI: 10.2527/jas.2010-2937
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dried distillers grains with solubles on carcass fat quality of finishing pigs1

Abstract: A total of 1,112 pigs (initial BW of 49.8 kg) were used in a 78-d study to evaluate the effects of 0, 5, 10, 15, or 20% dried distillers grains with solubles (DDGS) and sex on carcass fat quality of finishing pigs. All diets contained 6% choice white grease and were fed in 4 finishing phases (50 to 59, 59 to 82, 82 to 105, and 105 to 123 kg, respectively). The experiment was conducted in a commercial research finishing barn in southwestern Minnesota. There were 9 replicates of each dietary treatment, with 25 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
46
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 38 publications
19
46
2
Order By: Relevance
“…Total MUFA was found to have an inverse relation ship to total PUFA concentrations in all 3 fat depots evaluated in this study, which would agree with Benz et al (2010). Feeding tallow maintained similar concentra tions of total MUFA in all fat depots whether they were fed the additional fat for the duration of the study or only a single period when compared with those fed the control diet.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Total MUFA was found to have an inverse relation ship to total PUFA concentrations in all 3 fat depots evaluated in this study, which would agree with Benz et al (2010). Feeding tallow maintained similar concentra tions of total MUFA in all fat depots whether they were fed the additional fat for the duration of the study or only a single period when compared with those fed the control diet.…”
Section: Discussionsupporting
confidence: 78%
“…Processors that are measuring IV target a value of 73 to 75 g/100 g, with high values being less ideal (Benz et al, 2010). High IV values create challenges for processors, as the "soft fat" can create problems in belly slicing and reduce shelf life due to oxidative rancidity (NRC, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The changes in the fat IVs in pigs fed diets containing DDGS are most likely a result of the relatively large quantities of unsaturated fatty acids, particularly C18:2 in corn because the increases in dietary unsaturated fatty acid concentrations will increase the carcass fat IV. In the current study, the IV of the backfat and belly fat increased in pigs fed diets containing 300 g DDGS/kg, which agrees with previous reports (Benz et al, 2010;Dahlen et al, 2011), indicating that the IV of fat increased with increased DDGS content in grower-finisher pig diets. Regression analysis in the research has hundreds of pigs indicated that IVs increased 4.3 units for every 10 percentage unit inclusion of DDGS in the diet (Cromwell et al, 2011).…”
supporting
confidence: 93%
“…In the present study, the pigs fed the diets containing DDGS increased the percentage of C18:2 and PUFA, but the C16:0 and SFA decreased in both the backfat and belly fat. Similarly, Dahlen et al (2011), Benz et al (2010 and Xu et al (2010) observed changes in the fatty acid profiles of pigs fed increased dietary DDGS, Total PUFA = ((C18:2) + (C18:3) + (C18:3) + (C20:2) + (C20:4)). Means within a row with different superscripts differ (P < 0.05).…”
Section: Carcass Fat Qualitymentioning
confidence: 82%
“…other papers (Benz et al 2010;Rickard et al 2012) which reported an increase in IV as the concentration of DDGS increased. However, in this experiment, the fat concentrations between each group were similar and the lipid in diets was mainly supplied by corn oil and soybean oil.…”
Section: Fatty Acid Composition and Iodine Value Of Jowl And Belly Fatmentioning
confidence: 97%